2003
DOI: 10.1021/bi034683h
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Cysteine Residues in a Cytoplasmic Loop of CitS of Klebsiella pneumoniae Is Controlled by the Catalytic State of the Transporter

Abstract: The citrate transporter CitS of Klebsiella pneumoniae is a secondary transporter that transports citrate in symport with two sodium ions and one proton. Treatment of CitS with the alkylating agent N-ethylmaleimide resulted in a complete loss of transport activity. Treatment of mutant proteins in which the five endogenous cysteine residues were mutated into serines in different combinations revealed that two cysteine residues located in the C-terminal cytoplasmic loop, Cys-398 and Cys-414, were responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 32 publications
4
50
0
Order By: Relevance
“…Previous studies of the SSSCC mutant of CitS and cysteine mutants of the homologous transporter CimH of Bacillus subtilis showed, surprisingly, that residues in region Xa were accessible for membrane-impermeable MTS derivatives when presented at the periplasmic side of the membrane (11,27). The MTS derivatives are similar in size to citrate (32), and it was suggested that access from the periplasmic side of the membrane might follow (part of) the substrate translocation pathway (also see Ref.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies of the SSSCC mutant of CitS and cysteine mutants of the homologous transporter CimH of Bacillus subtilis showed, surprisingly, that residues in region Xa were accessible for membrane-impermeable MTS derivatives when presented at the periplasmic side of the membrane (11,27). The MTS derivatives are similar in size to citrate (32), and it was suggested that access from the periplasmic side of the membrane might follow (part of) the substrate translocation pathway (also see Ref.…”
Section: Discussionmentioning
confidence: 97%
“…The rate of uptake in RSO membranes prepared from E. coli cells expressing CitS and energized by the artificial electron donor system ascorbate/ PMS increased sigmoidally with increasing Na ϩ concentration. Half of the maximal rate was obtained at a Na ϩ concentration of 3 mM (27) (Fig. 2, q).…”
Section: Activity Of Single Cysteine Mutants Ssscs and Ssssc-mentioning
confidence: 93%
See 3 more Smart Citations